A method to restore Chinese warped document images based on binding characters and building curved lines - Hong Liu; Ye Lu (2009 IEEE International Conference on Systems, Man and Cybernetics, 2009)
With rapid development of information technology, more and more document images are made by scanners. But new problem comes out that many of document images from thick books are warped. It is quite inconvenient for further process on computer. This paper introduces an integrative algorithm on restoring Chinese document images, which is a new filed and few researchers have worked on this subject yet. The complicated structure of Chinese ¿block words¿ makes the problem more difficult. To solve this, a restoring method which is based on binding characters iteratively and building curved lines using parallel lines method is introduced. In the phase of fitting, SVR is adopted instead of other parameter methods. An idea of collaboration is also recommended to guarantee the quality of the final results. Correction rate of 94% for experiment of 300 document images proves this method works out very well.